A Needs Analysis of Computer and Network Engineering Program in Mataram Vocational Schools - Lela Rahmawati .; Abdul Hakim Yassi; Nasmilah; Abidin Pammu (Hasanuddin University, 2020)
The study is to reveal the significant different between the learning in Vocational School and in general Senior High School. The appropriate teaching-learning processes are based on their needs. The data in this study were qualitative descriptive data obtained through interviews and questionnaires. The questionnaires were distributed to the students and alumni of computer and network engineering program students. The data analyzed qualitatively. The aim of this study was to identify some factual information about the needs of vocational students in learning English, especially in the English-language skills (Listening, Speaking, Reading and Writing) and some of language components in English (Grammar & Vocabulary), and to analyze the conformity between the content of English textbooks with the vocational students’ needs. The subjects in this study were the vocational students and English textbooks, both SBC and Curriculum 2013 edition, of 4 (four) SMK which organized the TKJ department in Mataram. The results showed that the needs of students towards learning English is to meet the academic professions and the future needs of the students, which involved the skills of the language and some of the language components. Whereas in the case of conformity between the content of the English textbooks and the vocational students’ needs, it was found that the English textbooks was more focused on describing the English language competences generally and not directed to the Department of TKJ itself.